2004
DOI: 10.3171/spi.2004.100.1.0032
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical interlaminary vertebro- and kyphoplasty for severe osteoporotic fractures

Abstract: Object. Percutaneous vertebro- and kyphoplasty have become established methods for the treatment of uncomplicated osteoporotic vertebral fractures. In the setting of severe fractures involving fragmentation of the posterior wall and neural compromise, however, decompressive surgery cannot be performed and epidural cement leakage is poorly controlled. A microsurgical interlaminary approach for vertebro- and kyphoplasty was developed to allow spinal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 13 publications
1
36
0
4
Order By: Relevance
“…The small case series of Singh et al [12], shows good results following limited decompression and open VP/KP, at a short follow-up of 44 weeks. Boszczyk et al [13] showed similar results with interlaminar decompression and thecal sac mobilization, followed by VP/KP. In contrast to above, our series has 10 patients, with OVCF nonunion and significant spinal canal stenosis at thoracolumbar junction (cord level), who showed significantly improved clinical outcome at a longer follow-up of 38 months (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The small case series of Singh et al [12], shows good results following limited decompression and open VP/KP, at a short follow-up of 44 weeks. Boszczyk et al [13] showed similar results with interlaminar decompression and thecal sac mobilization, followed by VP/KP. In contrast to above, our series has 10 patients, with OVCF nonunion and significant spinal canal stenosis at thoracolumbar junction (cord level), who showed significantly improved clinical outcome at a longer follow-up of 38 months (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…This cement augmentation technique produces excellent outcomes in [85 % of patients treated [14]. However, percutaneous vertebroplasty for OVCF with IVC with DND may have been considered relatively contraindicated because of the possibility of neural complications induced by epidural cement leakage [4,10,14]. No definitive treatment of OVCF with IVC with DND has yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Boszczyk et al 16 described the injection of cement into the vertebral body directly through the posterior wall in 34 vertebrae of 24 patients during the application of a microsurgical approach in osteoporotic burst fractures with neurological involvement. The operator appears to be more confident with a trans-somatic access because the cement diffusion into the vertebral body is more easily controlled, while a trans-pedicular access might appear slightly more difficult also considering that Table 1 Summary of all patients who underwent intra-operative vertebroplasty.…”
Section: Resultsmentioning
confidence: 99%